Synthesis of the Key Saccharide Fragments of the Glucuronic Acid-Containing Repeat Unit of Pentosan Polysulfate, a Heparin Sulfate Mimetic - Banwell, Martin G.; Marshall, Sarah; Ward, Jas S.; Schwartz, Brett D. (SynOpen, 2023)
Suitably protected mono- and di-saccharide residues associated with the glucuronic acid-containing repeat unit related to pentosan polysulfate have been prepared. The stereo-controlled coupling, using trichloroacetimidate chemistry, of certain of these is also described and the structure of a disaccharide so-formed has been confirmed by single-crystal X-ray analysis.
Keywords: heparanase; mimetic; pentosan polysulfate (PPS); trichloroacetimidate; xylose